2011
DOI: 10.1038/aja.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels, phosphorylation and mammalian sperm capacitation

Abstract: Sexually reproducing animals require an orchestrated communication between spermatozoa and the egg to generate a new individual. Capacitation, a maturational complex phenomenon that occurs in the female reproductive tract, renders spermatozoa capable of binding and fusing with the oocyte, and it is a requirement for mammalian fertilization. Capacitation encompasses plasma membrane reorganization, ion permeability regulation, cholesterol loss and changes in the phosphorylation state of many proteins. Novel tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
227
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 274 publications
(236 citation statements)
references
References 168 publications
(263 reference statements)
2
227
0
7
Order By: Relevance
“…Capacitation is a complex maturational phenomenon that renders spermatozoa capable of binding and fusing with the oocyte, which is a requirement for mammalian fertilization. Capacitation encompasses plasma membrane reorganization, ion permeability regulation, cholesterol loss and changes in the phosphorylation state of many proteins (Visconti et al, 2011).…”
Section: Postepididymal Eventsmentioning
confidence: 99%
“…Capacitation is a complex maturational phenomenon that renders spermatozoa capable of binding and fusing with the oocyte, which is a requirement for mammalian fertilization. Capacitation encompasses plasma membrane reorganization, ion permeability regulation, cholesterol loss and changes in the phosphorylation state of many proteins (Visconti et al, 2011).…”
Section: Postepididymal Eventsmentioning
confidence: 99%
“…Asterisks indicate significant differences between compound and control buffer samples or between compound with or without VUANT (Mann-Whitney U, P < 0.01). The activation of insect sperm via ionotropic Ors is reminiscent of capacitation of mammalian sperm, which has been linked to signaling pathways mediated by metabotropic ORs (23,26,27) as well as the activity of several ionotropic channels (58,59). These include calcium channels, most notably the sperm cation channels, CatSpers (60)(61)(62)(63), potassium channels such as Kcnu1 (64,65) as well as sodium, proton, bicarbonate, and chloride channels that are localized along the sperm flagella and speculated to act downstream of receptors for diverse extracellular ligands (33,59).…”
Section: Significancementioning
confidence: 99%
“…Effect of Forskolin on Phosphorylation Events Associated with Sperm Capacitation-Capacitation is associated with the activation of a cAMP/PKA-dependent signaling pathway leading to phosphorylation of Ser/Thr residues in PKA substrates followed by up-regulation of protein tyrosine phosphorylation (1,45). It was previously shown that cAMP synthesized by sAC could stimulate phosphorylation of a number of PKA substrate proteins, so we asked whether a FK-induced increase in cAMP could up-regulate similar phosphorylation events in sperm.…”
Section: G␣ S Is Present In Mousementioning
confidence: 99%
“…They acquire fertilizing capacity during their transit through the female tract in a process known as capacitation. This process includes the preparation for a physiologically induced acrosome reaction and for changes in the sperm motility pattern known as hyperactivation (1). Although the molecular basis of this process is not completely understood, it has been shown that different aspects of capacitation are regulated by the second messenger cAMP (reviewed in Refs.…”
mentioning
confidence: 99%